ANALISIS PENGARUH KADAR HEMOGLOBIN PADA REMAJA PUTRI DENGAN KEJADIAN DISMENOREA - Rosita, Siskana Dewi; Mahmudah, Mutik (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
The height of anemia prevalence and dysmenorrhea on teenagers are as two health problems, but in fact, they do not really care with the symptom they feel, and take it as a normal situation. Anemia commonly caused by iron deficiency indicated with some symptom such as: tired, nervous, or sometimes get a shortness of breath so that bother the activities. In addition, when someone has anemia, the body sensitivity to pain will raise. The objective of the study is to analyze the influence of hemoglobin levels on teenagers with dysmenorrhea case. Observational analysis was used as the research method with the cross-sectional approach. The total population in this research was all the female teenagers in Dusun Kuntungan, Kragilan village, Sukoharjo Regency. The sampling technique applied was total sampling, and it took 26 teenagers. Interview answer sheet was used to obtain the data of dysmenorrhea case, and hemoglobin meter device was used to obtain the data of hemoglobin levels. The data was analyzed using Univariat and Bivariat of Chi-square test. The research finding shows Asimp.Sig is 0,01 (Asimp.Sig 0,01<0,05). It can be concluded that there is an influence between teenagers’ hemoglobin levels to the dysmenorrhea case. Keywords: Hemoglobin levels, Teenagers, Dysmenorrhea case